Case Report: Giant Epidermoid Cyst on the Neck with Hypopharyngeal Propulsion - Yayan Akhyar; Sukri Rahman (Journal of Agromedicine and Medical Sciences, 2021)
Introduction: Dermoid cyst is a cystic mass lined with stratified squamous epithelium with skin adnexal structure. Histopathologically dermoid cysts consist of 3 types, namely epidermoid cysts, true dermoid cysts and teratoid cysts. Epidermoid cysts are characterized by masses with a simple squamous epithelial lining. When the cyst ruptures, it releases a cheesy white matter that smells bad. Epidermoid cysts are most commonly found in the age range of 15 and 35 years with almost the same frequency between male and female sexes. Case description: We report a case of a 52-year-old man with a lump on the left side of the neck that has been slowly growing since 1 year and a computer tomography of the neck suspected a cyst in the anterior glottis. The patient was diagnosed as a neck cyst. Management was carried out by excision of the cyst under general anesthesia and histopathological examination with the results of an Epidermoid cyst. Conclusion: Epidermoid cysts can develop in any part of the body, but are very rare on the head and neck. Definitive management of epidermoid cysts with complete excision of the cyst gives satisfactory results Keywords: Giant Epidermoid Cyst, excision, hypopharyngeal propulsion